Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If 3*tanx*tany=1 then show that 2cos (x+y)=cos(x-y)

If 3*tanx*tany=1 then show that 2cos (x+y)=cos(x-y)

Grade:11

1 Answers

Arun
25763 Points
4 years ago
3 sinx siny= cosx cosy
now,
2 sinx siny= cosx cosy –sinx siny
cos(x –y) –cos(x+y) = cos(x+y)
now cos(x –y)= 2 cos(x+y)
hence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free